"Rapt Auditors!" Burke and the Revision of Rhetorical Violence in Wordsworth's The Prelude. Issue 3 (4th May 2019) - Hoffman-Schwartz, Daniel
ABSTRACT: In this essay, I return to Wordsworth's apostrophe to Burke in book 7 of the 1850 Prelude, arguing that this passage is best understood as a revisionary meditation on rhetoric. The address to Burke thus does not require that we leave behind the poetic to broach the question of the political, but instead forces us to examine rhetoric as the overdetermined crossing point of the political and the poetic. This conceptual frame becomes clear when one reads the passage immediately preceding, a skeptical account of a scene of political rhetoric; in this light, the plea for forgiveness from Burke is also legible as Wordsworth's own forgiving of rhetoric. The essay thus proceeds in two parts: the first section takes up the 1805 "critique" of political rhetoric (with reference to Empson's classic essay on "'Sense' in The Prelude "), arguing that Wordsworth in fact aims to save rhetoric from politics and thus institute a critical cut between poetry and politics; the second section addresses the 1850 "rehabilitation" of political rhetoric, arguing that Wordsworth's pointed usage of apostrophe and epideixis functions by contrast to demonstrate the irreducible intertwining of the poetic and the political.